Microfiber Fabry–Perot interferometer fabricated by taper-drawing technique and its application as a radio frequency interrogated refractive index sensor - Zhang, Jiejun (2013)
We propose a novel fiber Fabry–Perot interferometer (FPI) that incorporates a length of microfiber as its cavity and two fiber Bragg gratings (FBGs) as reflectors. The microfiber FPI is simply fabricated by flame-heated taper-drawing the central spot of an FBG into a section of microfiber. Ambient refractive index (RI) influences the effective index of microfiber, and thus the free spectrum range of the microfiber FPI, resulting in RI sensing. A dual-wavelength fiber laser based on the microfiber FPI is constructed, enabling radio frequency interrogation with high resolution. RI sensitivity of 911  MHz/RIU is experimentally demonstrated for microfiber FPI with equivalent diameter of 1.455 μm. Simulation results indicate that the sensitivity can be further enhanced by reducing the diameter of the microfiber.